2013
DOI: 10.4103/0975-7406.113301
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dental age, bone age and chronological age in underweight children

Abstract: Background and Objective:The knowledge of bone age and dental age is of great importance for pediatrician and pediatric dentist. It is essential for a pediatric dentist to formulate treatment plan and it is a source of complementary information for pediatrician. There are few studies, which showed the relationship between dental age, bone age and chronological age in underweight children. Therefore, objective of this study was to determine and compare dental age, bone age and chronological age in underweight c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
2
12
0
8
Order By: Relevance
“…Preadolescent Asian boys showed significant delays in bone age, particularly in middle childhood, when bone age lagged behind chronologic age by nearly 15 months. Children from Israel in 2013 and or from Korea in 2015 (12) with similar economies show remarkably similar results to those of white Americans (13), whereas undernourished Indian children show a much-retarded bone maturity (14).…”
Section: Human Variation Is Mostly Adaptivesupporting
confidence: 54%
“…Preadolescent Asian boys showed significant delays in bone age, particularly in middle childhood, when bone age lagged behind chronologic age by nearly 15 months. Children from Israel in 2013 and or from Korea in 2015 (12) with similar economies show remarkably similar results to those of white Americans (13), whereas undernourished Indian children show a much-retarded bone maturity (14).…”
Section: Human Variation Is Mostly Adaptivesupporting
confidence: 54%
“…(15) Kumar et al in 2013 performed a study on 14 to 18-year-olds based on the Demirjian method, and found a direct correlation between the dental age and weight of the male subjects. (18) Sadeghianrizi and colleagues explained the probable reasons for the accelerated dental growth in obese children. They stated that obese children in the pre-pubertal stage have a normal height despite the decreasing secretion of the growth hormone and the potential abnormality of the GH-insulin-like growth factor (IGF) system.…”
Section: -The Mean Difference Between the Estimated Dental Age And Chmentioning
confidence: 99%
“…10,11 Dişlerin olgunlaşmasının değerlendirilmesinde birçok amaçla hastadan rutin olarak alınan panoramik radyografilerin kullanılması basit bir prosedür olması ve minimal radyasyon dozu verilmesi açısından avantajlar taşımaktadır. 2,12 Radyografi üzerinde tespit edilen diş yaşının el-bilek radyografileri üzerinde tespit edilen kemik yaşı karşılaş-tırıldığı çalışmalara göre; [13][14][15] diş yaşı ve kemik yaşı bulgularının birbirleri ile uyumlu olduğunu, bulguların tek yumurta ikizlerinde paralellik gösterdiğini, ancak çift yumurta ikizlerinde uyumlu olmadığını belirtmişlerdir. 11 Aynı kemik yaşına sahip Türk çocuklarında erkek çocukların diş gelişiminin kızlara göre daha ileri olduğu ve pubertal büyüme atılımının tespitinde alt çene köpek dişi ile 1. küçük azı dişlerinin kök formasyonunun tamamlanması-nın olgunlaşma indikatörü olarak kullanılabileceğini belirtilirken, 16 Türk çocuklarda diş gelişiminin puberte döneminin indikatörü olarak kullanımını yetersiz olduğu belirtilen çalışmalar da bulunmaktadır.…”
Section: Diş Yaşıunclassified
“…Erken dönemde yapılan implantlarda bireyin kalan büyüme miktarı ile dişlerin mevcut sürme potansiyeli implantın göreceli olarak intrüzyonuna neden olabilmektedir. 15 Bu amaçla en az 6 aylık ara ile çekilen sefalometrik radyografilerin çakıştırılması, büyümenin en az 2 yıl süre ile takibi (boy artışının 0.5 cm/yıl'dan az olması beklenir) ve/veya kemik yaşı tayini kullanılmıştır. Sefalometrik radyografilerin çakıştırılması en güvenilir yaklaşım olarak belirtilmekte ancak uygulama sırasında zaman gerektirmesi implant yapılması için geç kalınmasına sebep olabilmekte ve tekrarlayan radyasyon dozları bir dezavavantaj oluşturmaktadır.…”
Section: İmplant Değerlendirmesiunclassified